Attitude toward Conflict and Family Business Succession (Journal of Business Management and Accounting, 2016)
Conflict is central in family business. Family business consists of family members working  together,  using  family  and  business  logics.  Efforts  are  done  to  mitigate  the impact of role conflicts. Nevertheless, conflict remains the top reason for discontinuity. Findings suggested that participants with positive attitude toward conflict take more relaxed  approach  toward  succession,  with  larger  next  generation  talent  pool.  This group  is  egalitarian  in  strategic  decision  making  and  characteristically  optimistic. Participants with negative attitude have a smaller talent pool for succession, since they reserve leadership for the select few. They are more cautious, requiring successors to implement their visions beforehand, and are less optimistic. This study contributes to the body of knowledge and family business practitioners. Firstly, this paper introduces the use of attitude toward conflict to predict behaviour during succession. Secondly, this  paper  inspires  leaders  to  assess  their  attitudes,  and  if  required  to  change  their attitudes, so that they can plan their succession accordingly.